2017
DOI: 10.1021/acs.accounts.7b00189
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Reactive Water and Hydrogen-Bonding Networks in Photosynthetic Oxygen Evolution

Abstract: In oxygenic photosynthesis, photosystem II (PSII) converts water to molecular oxygen through four photodriven oxidation events at a MnCaO cluster. A tyrosine, YZ (Y161 in the D1 polypeptide), transfers oxidizing equivalents from an oxidized, primary chlorophyll donor to the metal center. Calcium or its analogue, strontium, is required for activity. The MnCaO cluster and YZ are predicted to be hydrogen bonded in a water-containing network, which involves amide carbonyl groups, amino acid side chains, and water.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 53 publications
(178 reference statements)
3
22
0
Order By: Relevance
“…This observation presented the possibility that solvent molecules could play an important role in the spectroscopic signatures of molecular systems and more importantly, they could influence the mechanism of PCET in BiP-PF 10 . Similar observations have previously been reported on the role of water molecules in the prediction of the physical behavior of PSII (Barry et al, 2017;Saito et al, 2011;Sakashita et al, 2017).…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…This observation presented the possibility that solvent molecules could play an important role in the spectroscopic signatures of molecular systems and more importantly, they could influence the mechanism of PCET in BiP-PF 10 . Similar observations have previously been reported on the role of water molecules in the prediction of the physical behavior of PSII (Barry et al, 2017;Saito et al, 2011;Sakashita et al, 2017).…”
Section: Introductionsupporting
confidence: 90%
“…This observation presented the possibility that solvent molecules could play an important role in the spectroscopic signatures of molecular systems and more importantly, they could influence the mechanism of PCET in BiP–PF 10 . Similar observations have previously been reported on the role of water molecules in the prediction of the physical behavior of PSII ( Barry et al., 2017 ; Saito et al., 2011 ; Sakashita et al., 2017 ). Recent QM/MM studies by Saito and coworkers have suggested that the structured water molecules that were observed in the 1.9 Å resolution X-ray crystal structure of PSII could play a key role in shortening the distance between Y Z and its conjugate base partner, D1-His190.…”
Section: Introductionsupporting
confidence: 90%
“…The challenging 4-electron, 4-proton reaction is choreographed using a precisely tuned network of hydrogen-bonding interactions. 1 5 Efforts to design synthetic catalysts that mimic aspects of this microenvironment have primarily utilized distal interactions to orient water for O–O bond formation. These interactions have either been incorporated into the ligand, 6 11 or are assembled through the use of appropriate buffers.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrogen bonding interaction in biological chemistry is identified as crucial and has been a challenging study [44][45][46][47][48][49][50]. IR spectroscopy has proved to be a promising means of quantifying the hydrogen-bonding interaction in coal [46,51,52] and biomass [53][54][55][56].…”
Section: Introductionmentioning
confidence: 99%